Guanfacine enhances inhibitory control and attentional shifting in early abstinent cocaine-dependent individuals. (March 2015) - Fox, Helen; Sofuoglu, Mehmet; Sinha, Rajita
Objectives: Attenuation of adrenergic drive and cognitive enhancement, via stimulation of alpha2 pre- and post-synaptic receptors, may selectively enhance executive performance in early abstinent cocaine-dependent individuals. As these cognitive processes underpin important treatment-related behaviors, the alpha2 agonist, guanfacine HCl, may represent an effective pharmaco-therapeutic intervention. Methods: Twenty-five early abstinent cocaine-dependent individuals were administered a battery of neurocognitive tasks on entry into treatment (baseline) and again following 3 weeks of either placebo or guanfacine treatment (up to 3 mg). Tasks included: Stop Signal, Stroop, 3-Dimentional Intra-dimensional/Extra-dimensional (IDED) task, Spatial Working Memory (SWM), Paired Associates Learning (PAL), Verbal Fluency and the Rey Auditory Verbal Learning Test (RAVLT). Results: Compared with placebo, the guanfacine group demonstrated attenuated anxiety and negative affect as well as improved performance on selective executive tests. This included fewer directional errors on the stop signal task, fewer errors on the extra-dimensional shift component of the IDED task and better attentional switching during verbal fluency. Guanfacine did not improve strategic working memory or peripheral memory. Conclusion: Guanfacine improves selective cognitive processes which may underlie salient treatment-related regulatory behaviors. Alpha2 agonists may therefore represent important agents for cocaine dependence.